Case Report on Anti-Tubercular Drug Induced Hepatoxicity / Modified ATT - Khan, M Saru; Sunny, Basil; Krishnan, Rithuvaren M (Journal of Pharmacy Practice and Community Medicine)
This case summary focusing on a 67-year male patient admitted in Sun rise Hospital, Kochi with k/c/o active tubercular on cat.2 ATT, now patient came complaint with c/o decreased appetite, food intake, nausea, vomiting and excessive fatigability. The patient was received first line anti tubercular drugs 6 months back RHZE (Rifampin, Pyrazinamide, Ethambutol, and Isoniazid) and discontinued medication 2 months back. Now it is developed a severe hepatitis which is an adverse drug reaction of the Antitubercular drugs.
Keywords: Hepatitis; Adverse drug reaction of anti-TB drug; Treatment; Pulmonary Koch infection; ALT; AST; Modified att.